Unplanned Postoperative Angiography After Isolated Coronary Artery Bypass Grafting: State of the Art and Future Perspective - Konrad Wisniewski; Giovanni Concistrè; Angelo Maria Dell’Aquila (Medicina, 2025)
Unplanned postoperative coronary angiography (uCAG) following isolated coronary artery bypass grafting (CABG) represents a significant clinical challenge, reflecting postoperative myocardial ischemia (PMI) with substantial impact on outcomes. The incidence of uCAG varies from 0.39 to 5.3%, depending on institutional protocols and diagnostic thresholds. Elevated cardiac biomarkers (high-sensitivity troponin and CK-MB), ECG changes, and hemodynamic instability are key indicators guiding uCAG. While associated with increased short-term mortality and morbidity, timely identification and treatment of graft-related complications via uCAG can improve midterm survival. Percutaneous coronary intervention (PCI) often emerges as the preferred therapeutic strategy over redo CABG. Future efforts should focus on refining risk stratification models, expanding the role of non-invasive imaging modalities, and validating early intervention strategies through prospective studies. Establishing standardized criteria for diagnosing and managing PMI remains critical to enhance outcomes and healthcare efficiency.